Peripartum cardiomyopathy: case series from a tertiary care centre in India - Nalla, Lakshmi; Ragam, Akshitha Sai; Prakash, Vimarshitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Peripartum cardiomyopathy (PPCM) is a rare condition characterized by the onset of left ventricular systolic dysfunction and heart failure symptoms in the late stages of pregnancy or the early postpartum period. This paper presents a case series of Peripartum Cardiomyopathy (PPCM) from a tertiary care center in India. Seven cases are described, highlighting the diverse clinical presentations, diagnostic challenges, and treatment outcomes encountered. The majority of patients were young primigravidae, emphasizing the importance of considering PPCM even in low-risk individuals. Diagnosis relied on echocardiographic findings and exclusion of other causes of heart failure. Treatment strategies included pharmacological interventions aimed at reducing afterload, preload, and enhancing contractility. Despite the high mortality rate associated with PPCM, timely critical care managed by cardiologists prevented fatalities in our cohort. This series underscores the significance of early recognition, prompt referral, and collaborative management in optimizing outcomes for PPCM.